Patterns of infectious complications in acute myeloid leukemia and myelodysplastic syndromes patients treated with 10‐day decitabine regimen. (23rd October 2017) - Ali, Alaa M.; Weisel, Daniel; Gao, Feng; Uy, Geoffrey L.; Cashen, Amanda F.; Jacoby, Meagan A.; Wartman, Lukas D.; Ghobadi, Armin; Pusic, Iskra; Romee, Rizwan; Fehniger, Todd A.; Stockerl‐Goldstein, Keith E.; et al.
Abstract: Decitabine has been explored as a reduced‐intensity therapy for older or unfit patients with acute myeloid leukemia (AML). To better understand the risk of infections during decitabine treatment, we retrospectively examined the culture results from each infection‐related serious adverse event that occurred among 85 AML and myelodysplastic syndromes (MDS) patients treated in a prospective clinical study using 10‐day cycles of decitabine at Washington University School of Medicine. Culture results were available for 163 infection‐related complications that occurred in 70 patients: 90 (55.2%) events were culture‐negative, 32 (19.6%) were gram‐positive bacteria, 20 (12.3%) were gram‐negative bacteria, 12 (7.4%) were mixed, 6 (3.7%) were viral, 2 (1.2%) were fungal, and 1 (0.6%) was mycobacterial. Infection‐related mortality occurred in 3/24 (13%) of gram‐negative events, and 0/51 gram‐positive events. On average, nearly one third of patients experienced an infection‐related complication with each cycle, and the incidence did not decrease during later cycles. In summary, in patients receiving 10‐day decitabine, infectious complications are common and may occur during any cycle of therapy. Although febrile events are commonly culture‐negative, gram‐positive infections are the most frequent source of culture‐positive infections, but gram‐negative infections represent a significant risk of mortality in AML and MDS patients treated with decitabine. Abstract : To better understand the risk of infections during decitabine treatment, we retrospectively examined the culture results from each infection‐related serious adverse event that occurred among 85 acute myeloid leukemia (AML) and myelodysplastic syndromes (MDS) patients treated using 10‐day cycles of decitabine. On average, nearly one third of patients experienced an infection‐related complication with each cycle, and the incidence did not decrease during later cycles. The majority of neutropenic fevers were either culture‐negative or associated with gram‐positive bacteremia, although infection‐related mortality was primarily associated with gram‐negative bacteremia.